Antimicrobial Resistance Profile of Salmonella and Listeria monocytogenes Isolated from Products Marketed on the Border of Brazil with Argentina and Uruguay - Pereira, Juliano Gonçalves [UNESP]; Soares, Vanessa Mendonça; Tadielo, Leonardo Ereno [UNESP]; Ramires, Tassiana; da Silva, Wladimir Padilha (Elsevier, 2020)
We aimed to perform serotyping and the antimicrobial resistance profile of Salmonella spp. and Listeria monocytogenes strains isolated from raw meats imported illegally into Brazil along the borders of Argentina and Uruguay. Distinct isolates of Salmonella spp. (n ¼ 6) and L. monocytogenes (n ¼ 25) obtained from 270 of these food products of earlier work were serotyped and tested for antimicrobial resistance by agar disk diffusion method. For strains that were considered phenotypically resistant, antimicrobial resistance genes were investigated: strA, strB, floR, tetA, tetB, blaZ, blaTEM, ermB, ermC, and ereB to Salmonella sp. and blaZ and mecA to L. monocytogenes. All Salmonella isolates were identified as Salmonella Infantis; they were multidrug resistant and harbored the genes blaTEM (n ¼ 6), strA (n ¼ 1), strB (n ¼ 1), floR (n ¼ 1), ermB (n ¼ 1), tetA (n ¼ 3), and tetB (n ¼ 3). L. monocytogenes isolates belonged to serovars 1/2a (n ¼ 1), 1/2b (n ¼ 14), 1/2c (n ¼ 2), and 4b (n ¼ 8), showed resistance only to penicillin G (n ¼ 12), and did not show the blaZ and mecA genes. The results demonstrated that illegal foods that are commercialized in the Brazilian international border with Argentina and Uruguay may harbor foodborne pathogens, and some of them have multidrug resistance characteristics, such as Salmonella, emphasizing the need for greater control of international food transit in Brazil, especially in the region evaluated.
Keywords: Food; Genes; International trade; Multidrug resistance; Pathogens